Fatal intoxication of a regular drug user following N-ethyl-hexedrone and ADB-FUBINACA consumption. (July 2019) - Kovács, Katalin; Kereszty, Éva; Berkecz, Róbert; Tiszlavicz, László; Sija, Éva; Körmöczi, Tímea; Jenei, Nikolett; Révész-Schmehl, Hajnal; Institóris, László
Abstract: In Hungary, N-ethyl-hexedrone (NEH) was the most frequently seized stimulant designer drug in 2017, while among synthetic cannabinoids ADB-FUBINACA and AB-FUBINACA were the most popular. Symptoms of intoxication by these substances are well known but less is known about the pathology of overdose-related death. NEH-induced fatal intoxication has not been described in the literature and knowledge surrounding the particular circumstances of death could be useful better public education of risk and more adequate treatment of overdose patients. In this report, we characterize the case of a 23-year-old male regular drug user who died a few hours after NEH and ADB-FUBINACA consumption. His medical history showed arrhythmia in childhood, and some seizures. Autopsy found he had a BMI of 42.9, a hypertrophic and dilated heart, severe atherosclerosis of the valves, coronaries and the arteries, and edema of the internal organs. Histology confirmed those findings. Postmortem blood levels of NEH were 285 ng/ml, along with 0.08 ng/ml ADB-FUBINACA and five ADB-FUBINACA metabolites. Based on the blood concentrations measured in suspected drug users (≤83.9 ng/ml) we hypothesize that NEH intoxication was the cause of death in this case, with heart disease being a co-factor and that the synthetic cannabinoid effect might have been accompaniment. This case also offered the opportunity to identify the metabolites of ADB-FUBINACA in the blood. We identified metabolites in the post-mortem blood by comparing them to human liver microsomal enzyme metabolites in vitro. Three major and two minor metabolites were found in the blood, of which two could only be derived from ADB-FUBINACA, as opposed to other cannabinoids. The case highlights the importance of the complex analysis of drug related deaths by medico-legal autopsy, histopathology and toxicology. Highlights: 23 year-old man died after N-ethyl-hexedrone (NEH) and ADB-FUBINACA consumption. Autopsy and toxicological analysis concluded that the death was caused by the used NEH predisposed by cardiac changes. Autopsy findings were typical for regular stimulant and/or synthetic cannabinoid use. The blood concentration of NEH was extremely high (285 ng/ml), thought to be lethal. Besides 0.08 ng/ml ADB-FUBINACA five of its metabolites were identified in blood.